Progressive anonymity from identity politics to evidence-based government - Zack, Naomi, 1944- (Rowman & Littlefield, 2021)
"Continuing her visionary work in social-political philosophy, Zack critiques identity politics as perpetuating damaging essentialist perspectives and policies. The antidote to identity group egoism is anonymity based on relevant shared interests and a meritocracy led by experts chosen without preference for group affiliation or political charisma"--